Feminist Rights Equality Education And Occupation As Seen In Maya Angelou’s Poems - Derik Tri Fernandes (Fakultas Sastra Universitas Ekasakti, 2017)
The problem in this thesis is feminism in education, occupation and social as seen in Maya Angelou’s poems. Feminism is the struggle of movement women rights in economic, education, occupation, politic, social and different culture with men. In these poems, having the theme like struggle rights of women, women rights in self-confidence, hidden beauty, although the skills of her own feels more superior than men The finding in this analysis is 1). Angelou wants to voice the women must be more educated that can stand in patriarchal society, in basically women must get the rights equality in education like men. 2). Angelou wants to voice the women must get rights equality in occupation, like equality wages between men and women. 3). Angelou wants to voice nobody can do insult in physical or non-physical. In basically, degree of human its same front of Allah and society.